Miary podobieństwa obiektów symbolicznych : idea Gowdy i Didaya - Pełka, Marcin (Symbolic objects dissimilarity measures : Gowda and Diday idea, 2005)
This article presents symbolic dissimilarity measure proposed by Gowda and Diday. The aim of the article is to present all the parts of this idea and to characterize them. Article presents also suggestions of polish translations for words used by Gowda and Diday. At the and of the article some weaknesses of this idea were presented the possible usage of this idea was presented too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 69-75